Love for the neighbour in the moral philosophy of Immanuel Kant - Polyakova E. A. (Вестник Свято-Филаретовского института, 2024)
Kant’s philosophy directly addresses theological issues, one of which is the question of love for one’s neighbour. Its philosophical interpretation makes it possible not only to soften the rigorism of Kantian ethics, but also to resolve some of its characteristic paradoxes and to clarify the question of the concrete application of the categorical imperative. The article considers, in particular, the “paradox of method” used by Kant to define good and evil: evil is defined as reason’s abuse of its own freedom. It is precisely because of this understanding of evil that confidence in the moral quality of one’s own judgment becomes impossible. Kant even strengthens this point by introducing the notion of conscience as a self-judging reason, the latter being the strictest judge, whose verdict will always be accusatory. In order to avoid such undesirable conclusions, which leave no hope of justification in the face of the moral law, Kant introduces the concept of love for one’s neighbour as “a necessary addition to the imperfection of human nature”. True, such love, according to Kant, is impossible in respect to all people. But it is its presence in relation to some that allows us to overcome our own imperfection. Love for one’s neighbor precisely means voluntary recognition of the objective imperfection of one’s own subjective judgment about the morality and reasonableness of other people. And this recognition itself allows a person to rise to a moral height that would otherwise be inaccessible. In interpreting Kant’s ethics and, in particular, his concepts of reason and judgment, the author of the article relies on the concept of Joseph Simon, one of the leading modern German scholars of Kant studies in recent decades.